Impact of Green Supply Chain Management Practices on Performance of Manufacturing Companies in Jordan: A Moderating Role of Supply Chain Traceability - Muhammad Raza Mughal (LifeSciFi, 2019)
This study aims to measure the effect of GSCM practices on the performance of Jordanian manufacturing companies by investigating the moderating effect of supply chain traceability on the relationship between GSCM and organizational performance. This article follows a quantitative research design together with primary data collection through a survey questionnaire with the sample size considered in this study is 320 participants. For data analysis, Structural Equation Modeling (SEM) techniques are used, which include path assessment and Confirmatory Factor Analysis (CFA). The outcomes of this study confirm the significant effect of internal environment management, cooperation with customers, traceability, and eco-design on organisation performance. The findings also revealed a significant moderating impact of traceability on the relationship between eco-design and organisation performance, and on the association between internal environment management and organisation performance. The key limitation of this study has been associated with its limited scope, as this study was completely based on the manufacturing sector of Jordan. On the other hand, the absence of qualitative research design has been another major limitation of this study. The rising environmental concerns that revolve around the field of the supply chain is likely to increase the importance of GSCM practices. Hence, it is vital to investigate the impact that GSCM is likely to make on organisation performance.